Types of Internet Addiction Among Kazakhstan Students in the Digital Educational Space - Kariyev , Adlet; Orazbayeva , Fauziya; Zhunusbekova , Aziza; Kenzhetaeva , Roza (Insight: the psychological dimensions of society, 2025)
The aim of the work is to conduct theoretical and empirical research of the types of internet dependency among Kazakhstan students under conditions of the digital educational space. Methods. The study involved 390 students from the first to the fourth years of study at universities in Kazakhstan. To determine the types of Internet addiction, only those subjects who were classified as at risk (n = 257; 65.90%) and dependent (n = 62; 15.89%) were selected using the k-means method. Three valid methods were used to identify the studied psychocomplexes: “Internet Dependency Test” (IDT) by K. Young (1998); “Internet Addiction Test” (IAT) by T. Nikitina, A. Yegorov (2005), adapted by O. Kaminska (2014); “The Sixteen Personality Factor Questionnaire” (16PF) by H. Cattell, A. Mead (2008). Results. It was found that Internet addiction has the strongest inverse correlation with Internal tension (p < .001). It was emphasized that such personality traits as introversion, daydreaming, and lack of self-control have the strongest correlation with Internet addiction. Through k-means clustering analysis, the subjects were grouped into four clusters that reflected the types of Internet addiction: “Stable Internet Addiction”, “Controlled Internet Addiction”, “Radical Internet Addiction”, and “Open Internet Addiction”. Discussion and Conclusions. It was empirically investigated and theoretically substantiated that the types of Internet addiction are formed by the psychological complexes of relevant personal traits of the respondents who excessively use online resources (numerous mobile applications, enrolling in courses on educational platforms) during their educational and professional activities and who were appropriately classified into either the at-risk group or the addiction group. It was noted that the proposed classification allows for the systematization and deeper understanding of the scientific problem and the discovery of new scientific facts. It was recommended to implement the obtained results into the educational process of universities to develop preventive and psychocorrective programs for internet addiction.
Keywords: global computer network; addiction; norm; at-risk group; dependency; educational space; educational and professiona